Express (X²-16)/(X-1)(X+3) in partial fractions

(X2-16)/(X-1)(X+3) can be expressed as partial fractions as it is equivalent to A + B/(X-1) + C/(X+3) giving us : (X2-16)/(X-1)(X+3)≡ A + B/(X-1) +C/X+3). By multiplying both sides of this equation by (X-1) and (X+3) you get X2-16≡A(X-1)(X+3) + B(X+3) +C(X-1). This must be true for all values so to work out the variables A, B and C you start off by looking at the values of X which make the value of the bracket 0. These are X=1 and X=-3. When X=1: -15=4B, therefore B=-15/4. When X=-3: -7=-4C, therefore C=7/4. When the brackets are fully expanded the only X2 term is AX2 , therefore AX2=X2, therefore A=1.

SP
Answered by Sam P. Further Mathematics tutor

2166 Views

See similar Further Mathematics A Level tutors

Related Further Mathematics A Level answers

All answers ▸

Find the general solution to the differential equation: d^2y/dx^2 - 8 dy/dx +16y = 2x


Prove De Moivre's by induction for the positive integers


Integrate tan(x) wrt x


I don't understand how proof by mathematical induction works, can you help?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo

© MyTutorWeb Ltd 2013–2025

Terms & Conditions|Privacy Policy
Cookie Preferences